The Ciidae (Coleoptera: Tenebrionoidea) of the Maritime Provinces of Canada: new records, distribution, zoogeography, and observations on beetle-fungi relationships in saproxylic environments - Majka, Christopher G. (Zootaxa, 2007)
The Ciidae of the Maritime Provinces of Canada are surveyed. Fifteen species are now known to occur in the region, thirteen in Nova Scotia, six in New Brunswick, and two on Prince Edward Island. Ten new provincial records are reported. Seven species including Ceracis sallei Mellié, Ceracis thoracicornis (Ziegler), Cis creberrimus Mellié, Cis pistoria Casey, Cis subtilis Mellié, Malacocis brevicollis (Casey), and Orthocis punctatus (Mellié) are newly recorded in the Maritime Provinces as a whole. Cis americanus Mannerheim and Cis levettei (Casey) are newly recorded on Prince Edward Island, the first records of this family from the province. Collecting effort on Cape Breton Island, Prince Edward Island, and in New Brunswick has apparently been insufficient to fully document the ciid fauna of these areas. Some local and regional distribution patterns of ciids in the mainland of Nova Scotia and in the Maritime Provinces are suggested from the present data, but further collecting is required to confirm these. Zoogeographically, most of the region’s ciids are members of either a boreal fauna (9 species) with Holarctic affinities, or a southeastern North American Nearctic fauna (5 species). The Maritime Provinces ciid fauna has representatives of five of the six known ciid host-use groups. Records of host fungi indicate that there are suitable hosts for all species of ciids found in the region in all three Maritime Provinces, indicating that ciids in the region appear not to be limited by availability of suitable host-fungi. However, Cis horridulus Casey, Cis striolatus Casey, and Cis subtilis Mellié, the three species in the Trametes host-use group, are very infrequently collected and apparently rare. Forests in Maritime Provinces have been greatly affected by forestry and disease, and such activities are known to impact fungal communities. Consequently such practices could have important repercussions for groups like the Ciidae that are reliant on fungi as both a food source and a habitat